Antibody-drug conjugates in HER2-positive advanced or metastatic gastric cancer: a systematic review and meta-analysis - Li, Jiayang; Chen, Shuangyu; Chai, Yinying; Qiu, Shengliang (Frontiers in Oncology, 2025)
BackgroundAntibody-drug conjugates (ADCs) are an emerging therapy for HER2-positive advanced gastric cancer (AGC), yet their comparative efficacy and safety remain unclear. This systematic review and meta-analysis aimed to evaluate the clinical outcomes of different ADCs in this patient population.MethodsA systematic search of PubMed, Embase, Cochrane, and Scopus databases was performed to identify relevant studies. The primary endpoint was the pooled overall response rate (ORR), analyzed using a random-effects model. Safety, subgroup analyses, and publication bias were also assessed.ResultsTwelve studies comprising 1041 patients were included. The pooled ORR across all ADCs was 33.4% (95% CI, 26.3%–41.3%). Efficacy varied substantially among agents: trastuzumab deruxtecan (T-DXd) and DP303c demonstrated the highest ORRs (42.5% and 42.9%, respectively), whereas others, such as Trastuzumab emtansine (T-DM1), showed lower efficacy (20.6%). ORR was not significantly affected by prior treatment lines (P = 0.6559) or cohort type (P = 0.7185). The most common adverse events included nausea (47.7%), with grade ≥3 anemia (21.1%) and neutropenia (15.1%) being the most frequent severe toxicities.ConclusionsThe efficacy of ADCs in HER2-positive AGC is highly variable. T-DXd and DP303c appear to be the most active agents, underscoring the critical importance of specific drug selection. Managing toxicities such as anemia and neutropenia is essential for optimizing treatment. Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420250653886, identifier PROSPERO CRD420250653886.